THE ADDITION OF ANDALIMAN FRUIT (Zanthoxylum acanthopodium DC) ON THE QUALITY OF CATFISH (Pangasius hypophthalmus) MEATBALLS DURING ROOM TEMPERATURE STORAGE - Martahan Gabema S; N. Ira Sari; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aims to determine the additional effect of andaliman fruit (Zanthoxylum acanthopodium DC) on the quality of catfish (Pangasius hypophthalmus) meatballs during room temperature storage. The method used in this research was an experimental method that was the processing of catfish meatballs with the addition of andaliman fruit 0%, 1%, 1.5%, 2% for 6, 12, and 18 hours of room temperature storage. Catfish meatballs with the addition of andaliman fruit during room temperature storage were significantly affected by organoleptic values (appearance and taste), water content, and total bacterial colonies, however, were not significantly affect the value of aroma, texture, and protein content at 95% of confidence level. Based on the results of research the addition 2% of andaliman fruit on catfish meatballs during room temperature storage for 18 hours of shelf life was most preferable by consumer acceptance with organoleptic values of appearance 3.41, aroma 3.39, taste 3.48, and texture 3.32, while the water content was 66.29%, protein 13.18%, and the total bacterial colony was 2.7x103 cells/gram. Keywords: Fish meatballs, andaliman concentration, proximate analysis.